Partnership in Participative Leadership and Organizational Communications: Factors Shaping Junior High School Teacher Performance - Balqis, Suci Nabilah; Usman, Nasir; Ismail (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This study aims to analyze the influence of participative leadership by school principals and organizational communication on teacher performance at junior high schools (SMP) in Banda Aceh. The research uses a quantitative method with an ex post facto approach. The sample consists of 76 teachers proportionally selected from six public junior high schools accredited A and B, using Slovin's formula. Data were collected through closed questionnaires and documentation and then analyzed using descriptive statistics, linear regression tests, and validity tests with the help of SPSS 26.0. The results of the study show that participative leadership by the principal and organizational communication have a significant influence on teacher performance. The significance value from the regression test indicates that both participative leadership (sig = 0.005) and organizational communication (sig = 0.000) significantly affect teacher performance. Additionally, the F-test also shows that both independent variables simultaneously have a significant influence on teacher performance (F = 20.9, sig = 0.000). This study emphasizes the importance of participative leadership and good organizational communication in improving teacher performance at the junior high school level, particularly in Banda Aceh.